A bipartite network analysis of international trade volatility - John Schoeneman; Marten Brienen; Lixia Lambert; Dayton Lambert (Applied Network Science, 2024)
Abstract This study examines the unprecedented global trade disruptions caused by the COVID-19 pandemic and their propagation through international supply chains. By analyzing monthly data for 75 countries across 1260 product categories, we find that declining trade disruptions are more concentrated than surge disruptions, indicating a broader impact of negative shocks on global trade. Our findings also suggest that disruptions in export flows tend to have a more significant effect than imports and that trade disruptions within a given commodity are more likely to spread to other countries trading in that same commodity rather than to other commodities traded by the same country. These insights offer lessons for firms and policymakers seeking to mitigate the effects of future exogenous shocks on global markets and supply chains.